INTEGRASI SISTEM PENDIDIKAN DAYAH DARUSSA’ADAHCOT TAROM BAROH MELALUI MADRASAH - Saifuddin; Diana; Liza Mutia (Indonesian Journal of Islamic and Social Science, 2023)
The problem of this research is how the form of integration and implications of the Islamic boarding school education system through madrasas at Darussa'adah Cot Tarom Baroh Islamic boarding school. This study aims to determine the form of integration and its implications for the Darussa'adah Cot Tarom Baroh Islamic boarding school education system through the madrasas that were established therein. This study used a qualitative method, namely field research. The research findings inform: the forms of integration of the Darussa'adah Cot Tarom Baroh Islamic boarding school education system through Madrasahs are the integration of religious and general knowledge, integration of formal and non-formal curricula, and integration of extracurricular activities. Then the implications of this integration are in the learning and quality of students. The implications for learning can be proven by the advancement of Islamic boarding schools, Islamic boarding schools are able to develop the curriculum and the potential of students from the addition of the madrasah learning curriculum. While the implications for the quality of the students can be proven by the achievements of the students, both in learning and competitions, and can also be seen from the spiritual attitude of the students.